Differences in the Levels of Physical Activity and Sport Habits between Men and Women in Cartagena (Spain) - Celia Armada; Bernardino Javier Sánchez-Alcaraz; Javier Courel-Ibáñez; Eduardo Segarra-Vicens (MDPI AG, 2024)
Scientific evidence proves the importance of physical activity and sports in decreasing morbidity and mortality rates and health-related costs. Public and stakeholder involvement is vital in the sustainable promotion of physical activity and sports practice in local settings. The aim of this study was to identify the levels of physical activity and sports habits of the population of the city Cartagena (Spain). The short version of the International Questionnaire of Physical Activity was used (IQPA) and a virtual questionnaire on sports habits was sent to 1450 citizens. Responses from 248 people (162 men and 86 women), with ages ranging from 18 to 77 years old (average age = 41 ± 17 years old), were collected. The results showed low to moderate levels of physical activity with no considerable differences between men and women for the population of Cartagena. Women were shown to engage in higher intensity practice of physical activity, whereas men were shown to be more consistent and have a significantly higher participation rate in sports events, both those with free entry and those that require the acquisition of a ticket. Men were also shown to have a higher rate of media sport use. This information may assist in the development of effective political actions to promote physical activity and sports in local settings.